Urgensi Filsafat Dakwah dalam Meningkatkan Kompetensi Calon Praktisi Dakwah - Bachtiar, M. Anis (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This paper seeks to explain the urgency of the philosophy of da'wah for developing students' understanding of da’wah science-related units in the Department of Islamic Communication and Broadcast, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya. Applying a library and field research, this study has found that the da’wah philosophy unit has contributed to the increase of students' understanding about the scope and area of da'wah science. In addition, the unit of da'wah philosophy has provided philosophical methodology that is useful for examining the process of da'wah, including critical thinking, for those who are candidate of Islamic preachers (da’i), namely the students of Da’wah and Communication Faculty.